Utilization of salt‐rich by‐products from the dairy industry as feedstock for recombinant protein production by Debaryomyces hansenii. Issue 2 (24th November 2022) - Estrada, Mònica; Navarrete, Clara; Møller, Sønke; Procentese, Alessandra; Martínez, José L.
Abstract: The dairy industry processes vast amounts of milk and generates high amounts of secondary by‐products, which are still rich in nutrients (high Chemical Oxygen Demand (COD) and Biochemical Oxygen Demand (BOD) levels) but contain high concentrations of salt. The current European legislation only allows disposing of these effluents directly into the waterways with previous treatment, which is laborious and expensive. Therefore, as much as possible, these by‐products are reutilized as animal feed material and, if not applicable, used as fertilizers adding phosphorus, potassium, nitrogen, and other nutrients to the soil. Finding biological alternatives to revalue dairy by‐products is of crucial interest in order to improve the utilization of dry dairy matter and reduce the environmental impact of every litre of milk produced. Debaryomyces hansenii is a halotolerant non‐conventional yeast with high potential for this purpose. It presents some beneficial traits – capacity to metabolize a variety of sugars, tolerance to high osmotic environments, resistance to extreme temperatures and pHs – that make this yeast a well‐suited option to grow using complex feedstock, such as industrial waste, instead of the traditional commercial media. In this work, we study for the first time D. hansenii's ability to grow and produce a recombinant protein (YFP) from dairy saline whey by‐products. Cultivations at different scales (1.5, 100 and 500 ml) were performed without neither sterilizing the medium nor using pure water. Our results conclude that D. hansenii is able to perform well and produce YFP in the aforementioned salty substrate. Interestingly, it is able to outcompete other microorganisms present in the waste without altering its cell performance or protein production capacity. Abstract : The halophilic yeast Debaryomyces hansenii has been succesfully used to produce a recombinant fluorescent protein, using salty by‐products from the dairy industry as fermentation feedstock, in controlled lab‐scale bioreactors.